Simulation of pH level distribution inside a coiled flow inverter for continuous low pH viral inactivation. Issue 2 (12th November 2019) - David, Laura; Waldschmidt, Lisa Marie; Lobedann, Martin; Schembecker, Gerhard
Abstract: The continuous production of monoclonal antibodies (mAbs) with the help of disposable equipment poses one of the future major changes in the pharmaceutical industry. Consequently, continuous viral clearance needs to be developed as well. The coiled flow inverter (CFI) was successfully implemented in the continuous downstream as a residence time module for low pH viral inactivation. As the elution profile of the upstream continuously operated protein A chromatography results in fluctuating pH values, the pH level distribution inside the CFI is highly relevant. This study presents a detailed investigation of pH level distribution inside the CFI at varying inlet conditions with the help of computational fluid dynamics simulation. The simulation model was validated first with the help of experimental data. Afterwards, the model was used for further investigations. It was determined that with a pH sine curve as input, the duration until steady state at the outlet requires two times the minimum residence time of the apparatus. Moreover, it could be observed that the CFI itself offers a progressive dampening effect on the pH level distribution. Afterwards, different forms of the sine curve representing different operation modes of the continuous protein A chromatograph were tested to evaluate this dampening capability. It became clear that the switch time has the highest influence on the resulting pH of the outlet stream and should be considered for process development. Finally, the radial pH profiles at different positions inside the CFI were determined. This once again revealed the high radial mixing capability of the CFI and its influence on the resulting product stream. Abstract : The continuous production of monoclonal antibodies (mAbs) with the help of disposable equipment poses one of the future major changes in the pharmaceutical industry. Consequently, continuous viral clearance needs to be developed as well. The coiled flow inverter (CFI) was successfully implemented in the continuous downstream as a residence time module for low pH viral inactivation. As the elution profile of the upstream continuously operated protein A chromatography results in fluctuating pH values, the pH level distribution inside the CFI is highly relevant.